Pengaruh Kualitas Pelayanan Dan Transparansi Terhadap Minat Muzakki Membayar Zakat, Infak Dan Sedekah Di Lembaga Amil Zakat Khairul Ummah Kabupaten Indragiri Hulu - Sonyatul Jannah; Viras Alti Pidola (CV. ITTC INDONESIA, 2025)
This study aims to analyze the influence of service quality and transparency on the interest of muzakki in paying zakat, infaq, and sadaqah at the Khairul Ummah Zakat Institution in Indragiri Hulu Regency. This is motivated by the fact that fund collection has not been optimal compared to the existing potential. Service quality and transparency are important factors in enhancing donors' interest and trust in paying zakat, infak, and sedekah at the institution. This study employs a quantitative research method with data collection techniques including questionnaires, interviews, and documentation. The sample consists of 87 respondents, selected using simple random sampling. The data analysis techniques employed include classical assumption tests, multiple linear regression analysis, and hypothesis testing. Based on the results processed using SPSS version 23, the R Square value is 0.726, indicating that 72.6% of donors' interest is influenced by the variables of service quality and transparency, while the remaining 27.4% is influenced by factors outside the scope of this study. The F-test results showed that the calculated F value of 111.333 > the table F value of 3.10 with a significance level of 0.000 < 0.05, meaning that service quality and transparency simultaneously have a significant effect on the interest of zakat payers in paying zakat, infak, and sedekah at the Khairul Ummah Zakat Management Institution in Indragiri Hulu District. The t-test results show that the service quality variable has a calculated t-value of 4.884 > t-table 1.989 with a significance of 0.000 < 0.05, and the transparency variable has a calculated t-value of 4.308 > t-table 1.989 with a significance of 0.000 < 0.05, meaning that service quality and transparency have a positive and significant influence on the interest of muzakki in paying zakat, infak, and sedekah at the Khairul Ummah Zakat Management Institution in Indragiri Hulu District.